Anisotropic drop spreading on superhydrophobic grates during drop impact. Issue 19 (27th April 2018) - Han, Jeonghoon; Ryu, Seunggeol; Kim, Hyunsik; Sen, Prosenjit; Choi, Dukhyun; Nam, Youngsuk; Lee, Choongyeop
Abstract : We study the influence of geometric anisotropy of micro-grate structures on the spreading dynamics of water drops after impact. Abstract : We study the influence of geometric anisotropy of micro-grate structures on the spreading dynamics of water drops after impact. It is found that the maximal spreading diameter along the parallel direction to grates becomes larger than that along the transverse direction beyond a certain Weber number, while the extent of such an asymmetric spreading increases with the structural pitch of grates and Weber number. By employing grates covered with nanostructures, we exclude the possible influences coming from the Cassie-to-Wenzel transition and the circumferential contact angle variation on the spreading diameter. Then, based on a simplified energy balance model incorporating slip length, we propose that slip length selectively enhances the spreading diameter along the parallel direction, being responsible for the asymmetric drop spreading. We believe that our work will help better understand the role of microstructures in controlling the drop dynamics during impact, which has relevance to various engineering applications.